Quasi-phase-matched high-harmonic generation in gas-filled hollow-core photonic crystal fibre - Wiegandt, AFCL (2020)
High-order harmonic generation (HHG) provides a promising tabletop source of coherent short wavelength radiation. However, the low generation efficiency limits the mean photon flux of HHG sources when driven with low average power, kHz repetition rate lasers. The HHG flux could be increased by employing MHz repetition rate driving lasers. However, the low pulse energy necessitates tight focusing, which limits the effective interaction volume. Generating harmonics in a gas-filled photonic crystal fiber (PCF) mitigates this problem, but for both free focus and PCF targets, the HHG conversion efficiency is optimized at technologically challenging multi-bar gas pressures. In this thesis, HHG is performed with µJ-level driving pulses in hollow-core PCFs. Dramatic 160-fold enhancement of the HHG flux through a novel, time-multiplexed multi-modal quasi-phasematching technique is observed at low gas-pressures. Non-phase-matched generation of high-harmonic photon energies up to 61.6 eV with continuous spectral tunability made possible by controlled ionization-induced blue-shifting of the driving laser is presented and fully phase-matched HHG in an argon-filled PCF is explored.